President of the Irish Freestate De Valera (second from the right) at the Royal Dublin Society's Horse Show in Dublin. Right: viscount Powerscourt. Left: Pack Beresford and lady Powerscourt. Text on the back
President of the Irish Freestate De Valera (second from the right) at the Royal Dublin Society's Horse Show in Dublin. Right: viscount Powerscourt. Left: Pack Beresford and lady Powerscourt. Text on the back.